Children's errors in mathematics : understanding common misconceptions in primary schools - Hansen, Alice; Drews, Doreen; Dudgeon, John. (Exeter : Learning Matters, 2007)
This book is a reference guide to children's common errors and misconceptions in mathematics. It is ideal for anyone training to teach 4-11 year old children and interested in enhancing their understanding of the difficulties children exhibit during their mathematical development
Includes references.
Keywords: Mathematics -- Study and teaching (Elementary -- Great Britain; Mathematics -- Study and teaching (Elementary)